Silicon as Versatile Player in Plant and Human Biology: Overlooked and Poorly Understood - Farooq, Muhammad Ansar; Dietz, Karl-Josef (Frontiers in Plant Science, 2015)
Silicon (Si) serves as bioactive beneficial element. Si is highly abundant in soil, and occurs ubiquitously in all organisms including plants and humans. During the last three decades, nutritional significance of Si for plant and human health has received increasing attention. Plant Si plays a pivotal role in growth and development, and this beneficial effect depends usually on accumulation in plant tissues, which are then protected from various forms of biotic and abiotic stresses. Likewise, human exposure to Si imparts health benefits and essentially occurs through plant-derived food products. Si bioavailability in human diet, e.g., strengthens bones and improves immune response, as well as neuronal and connective tissue health. Despite this empiric knowledge, the essentiality of Si still remains enigmatic. Thus the link between Si availability for plant development and its profound implication for human welfare should receive attention. This review aims to provide a broad perspective on Si as important element for plant and human nutrition and to define research fields for interdisciplinary research.